Effect of Internal Control Systems on Financial Performance of Commercial Banks - Claudia Tusiime (Uganda Christian University, 2023)
The study examined the effect of internal control on financial performance of Equity Bank. The Specific Objectives of the study were to examine the effect of control environment on financial performance of Equity bank, the effect of risk assessment on financial performance of Equity bank and the effect of control activities on financial performance of Equity bank. The study used a descriptive cross-sectional design using both qualitative and quantitative approach to collect data from a sample of 59 respondents. Questionnaires were used to collect the data. Quantitative data was analysed using measurement of central tendency and qualitative data was analysed using correlations and regression analysis techniques. The study found a good relationship between control environment and financial performance. The study also found a high positive significant relationship between credit risk assessment and financial performance. Then the study found a high positive significant relationship between control activities and financial performance The study concluded that the presence of internal control reduces chances of committing fraud among the staff and other members of the organization. The management of every commercial bank has a duty of setting up internal control system and monitoring their performance. The system should work effectively for the purpose of identifying and preventing frauds from happening when this happens the bank is in a better position of performing well financially. The system should be well accessed, and its performance scrutinized over time by the management for effective performance. The internal controls play a major role in providing accurate measurements of data. The study recommends that universal banks should pay attention to monitoring through providing independent process checks and evaluation of control activities on on-going basis and ensuring internal reviews of implementation of internal controls in units are conducted periodically.